2004
DOI: 10.7498/aps.53.3211
|View full text |Cite
|
Sign up to set email alerts
|

Exciton tunnelling in ZnCdSe quantum well/CdSe quantum dots

Abstract: Exciton tunneling through ZnSe barrier layer of various thicknesses is invest igated in a novel Zn072Cd028Se/CdSe coupled quantum well/quantum dots (QW/QDs) structure using photoluminescence spectra and nearresonant pumpprobe mea surements. Fast exciton tunneling from quantum well to quantum dots is observed by transient differential transmission. The tunneling time is 18ps, 44ps, 39 ps for barrier thickness of 10nm, 15nm, 20nm, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…For example, in an investigation by Saito and Kayanuma [33], it was shown that a ballistic Wannier exciton exhibits tunnelling resonances through a single barrier heterostructure by the same mechanism as discussed in this paper and our previous studies. The methods and results in our investigation are applicable to experimental and theoretical research involving the tunnelling of excitons [34].…”
Section: Connection With Realistic Systemsmentioning
confidence: 94%
“…For example, in an investigation by Saito and Kayanuma [33], it was shown that a ballistic Wannier exciton exhibits tunnelling resonances through a single barrier heterostructure by the same mechanism as discussed in this paper and our previous studies. The methods and results in our investigation are applicable to experimental and theoretical research involving the tunnelling of excitons [34].…”
Section: Connection With Realistic Systemsmentioning
confidence: 94%
“…Finally, as reported in Refs. [21,22], there is excitation energy transfer from small QDs to large ones through tunnelling effects, and as a result, the PL intensity at the long wavelengths is higher than that at the shorter wavelengths. In addition, it is seen that the emission peaks show a red-shift with respect to the lowest 1S-1S absorption for all the four samples.…”
Section: Results and Analysismentioning
confidence: 99%